The Social Media Debate: Unpacking the Social, Psychological, and Cultural Effects of Social Media - Kiraz, Ersel (Süleyman Demirel Üniversitesi, 2024)
‘The Social Media Debate: Unpacking the Social, Psychological, and Cultural Effects of Social Media’, published in 2022, consists of 14 different chapters and examines social media within the framework of “Social, Psychological, and Cultural Effects”. ‘The Social Media Debate: Unpacking the Social, Psychological, and Cultural Effects of Social Media’ is a scholarly work that examines the multifaceted effects of social media on individuals and society in depth. Editor Devan Rosen and other expert authors examine the effects of social media on sociocultural dynamics, mental health, information pollution, data privacy, and marginalised communities. The book offers a balanced view of the positive and negative aspects of social media use, analysing from a variety of perspectives how social media platforms shape individuals' behaviour and power relations in society.

2022 yılında yayınlanan “The Social Media Debate: Unpacking the Social, Psychological, and Cultural Effects of Social Media” başlıklı kitap 14 farklı bölümden oluşmakta ve sosyal medyayı “Sosyal, Psikolojik ve Kültürel Etkiler” çerçevesinde incelemektedir. “The Social Media Debate: Unpacking the Social, Psychological, and Cultural Effects of Social Media”, sosyal medyanın bireyler ve toplum üzerindeki çok yönlü etkilerini derinlemesine ele alan bilimsel bir çalışma. Editör Devan Rosen ve alanında uzman diğer yazarlar, sosyal medyanın sosyokültürel dinamikler, ruh sağlığı, bilgi kirliliği, veri gizliliği ve marjinal topluluklar üzerindeki etkilerini inceliyor. Kitap, sosyal medya platformlarının bireylerin davranışlarını ve toplumdaki güç ilişkilerini nasıl şekillendirdiğini çeşitli perspektiflerden analiz ederken, sosyal medya kullanımının olumlu ve olumsuz yönlerine dair dengeli bir bakış açısı sunuyor.
Bir Sosyal Medya Tartışması: Sosyal Medyanın Sosyal, Psikolojik ve Kültürel Etkileri
Keywords: Social Media Studies; Sosyal Medya Çalışmaları